Students Science Literacy Differences Based on Gender Using Project Based Learning Model - Any Fatmawati; Baiq Muli Harisanti; Titi Laily Hajiriah; I Wayan Karmana (Postgraduate, University of Mataram, 2024)
Science literacy has become one of the skills needed to prepare a young generation that is adaptive to the advances of science and technology in the 21st century. According to research by some experts, the literacy of science students in Indonesia is still low. The reason for the poor science literacy of students is that they are not activated continuously in the learning process. Therefore, there is a need for the application of innovative learning models, one of which is the project-based learning (PjBL) model. The PjBL model phase is useful to train students to be responsible for their own learning and develop their ability to think systematically. The gender of students, consisting of men and women, is important to note because it relates to several things, including thinking skills, decision-making, and the ability to draw conclusions. All these abilities are supportive factors of student science literacy, so it is necessary to conduct a study of differential science literacy by differentiating the gender of students. The research was conducted at SMAN 7 Mataram Nusa Tenggara West (NTB) with quasi-experiments. The subject of the study is class X students, consisting of 5 parallel classes, with a total number of 126 people (44 males and 82 females). The free variable in research is the PjBL model, and the bound variable is science literacy. Research instruments for science literacy use essay questions. The results of the study showed that the average science literacy of female students is 55.99; this figure is higher than the male literacy score of 53.03. Furthermore, the Anova test result shows that the significance value at the level of 5% is 0.62 ≥ 0.05, so it can be concluded that there is no significant difference in the literacy value of male and female science students after learning using the PjBL model.